KONFIRMASI FLU BABI A/H1N1 MENGGUNAKAN PCR - A.A. Wiradewi Lestari; I.A. Putri Wirawati; Tjok Gde Oka (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
Swine Influenza (2009 H1N1) is a new influenza virus causing illness in people. This new virus was first detected in the United Statespeople, April 2009. This virus probably spread the same way worldwide from person-to-person much as the regular spreading of commonseasonal influenza viruses. A 13 years old male entered the hospital with fever, cough and sore throat. Before he was hospitalized, hehad travelled to Batam for four (4) days. A PCR test from throat and nasal swabs were taken, and found positive for influenza A andswine H1 (as confirmed case for swine influenza A/H1N1). After taking oseltamivir for 5 days and the second PCR test negative, thepatient is released from the hospital.